Cultivation of Lentinus Edodes on Teff Straw (Agricultural Residue) at Dilla University, Ethiopia - Alemu, Fekadu (The Asia Journal of Applied Microbiology, 2014)
Shiitake mushroom is worldwide one of the most widely cultivated mushrooms. Edible fungi are natural recycler which converts lignocelluloses wastes into protein rich health food and medicinal value of food. Mushroom cultivation represents the current economically viable biotechnology process for the conversion of waste plant residues from agriculture. As the result, mushrooms are increasingly becoming an important component of diets worldwide and it is of paramount importance to choose appropriate substrates in a given place to grow them. Therefore, study was undertaken to find suitable abundantly waste such as Teff straw used as substrate for cultivation of mushroom. As the result revealed, this agricultural residue was the best for cultivation of Lentinus edodes which help to collect large amount of fruit body. As conclusion, Lentinus edodes fungi can be converted this solid waste in to delicious foods.